Efficacy of an Internet-Based Intervention for Subclinical Depression (MoodBox) in China: Study Protocol for a Randomized Controlled Trial - Chen, Xu; Zhang, Xiaolong; Zhu, Xuequan; Wang, Gang (Frontiers in Psychiatry, 2021)
Background: Subclinical depression is a prevalent mental health problem and increases the incidence of the onset of major mood disorders, such as major depressive disorder. Psychological interventions have been proved to be effective for reducing depressive symptoms for people with subclinical depression and can prevent the onset of major depressive disorder. However, people have limited access to face-to-face psychotherapy. Internet-based psychological intervention is an alternative treatment option. The aim of the study is to evaluate the efficacy of MoodBox, an online psychological intervention program, for subclinical depression. Methods: This study is a multicenter, randomized, controlled, non-blinded superiority study with three parallel groups. A total of 435 first-year university students with subclinical depression participants will be recruited. Eligible participants will be randomly assigned to the MoodBox group, the online psychoeducation group, and the naturalistic observation group at a ratio of 1: 1: 1. The intervention period is eight weeks, and participants will be continuously followed-up to one year. The primary outcome of the study is the efficacy of the intervention, defined as measured by the Patient Health Questionnaire (PHQ-9). Discussion: This is the first study to innovatively develop and test an intervention to improve psychological well-being and decrease the incidence of MDD in subclinical depression population in China. Once proven effective and acceptable, Moodbox could be potentially integrated into the routine clinical service to facilitate the management for people with subclinical depression. Clinical Trial Registration: The trial is registered with the Chinese Clinical Trial Registry on 21 July 2020 (No. ChiCTR2000034826).